2018
DOI: 10.1108/lodj-11-2016-0298
|View full text |Cite
|
Sign up to set email alerts
|

Why and when leadership training predicts effectiveness

Abstract: People interested in the research are advised to contact the author for the final version of the publication, or visit the DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the author… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 59 publications
1
19
0
Order By: Relevance
“…This is because their leader identity is likely to be stable given the breadth and the depth of leadership experience. For example, Kragt and Guenter (2018) found that the identity of inexperienced leaders was more affected by leadership training than that of experienced leaders.…”
Section: Leader Identity Developmentmentioning
confidence: 99%
“…This is because their leader identity is likely to be stable given the breadth and the depth of leadership experience. For example, Kragt and Guenter (2018) found that the identity of inexperienced leaders was more affected by leadership training than that of experienced leaders.…”
Section: Leader Identity Developmentmentioning
confidence: 99%
“…On the other hand, literature suggests that more experienced managers possess a more complex set of knowledge, skills, and abilities required for the leadership role, which allows them to become more effective in their leadership role (cf. Kragt & Guenter, 2018). In addition, having experience from other managerial job positions, which often is the case when managerial tenure is high, provides the manager with opportunities to learn to adjust and to cope with different environments (Bettin & Kennedy, 1990).…”
Section: The Moderating Effect Of Managers' Tenurementioning
confidence: 99%
“…The question was answered on a continuous response scale. Similar to other scholars (Kragt & Guenter, 2018), focus in this study is on formal tenure as an indication of experience because it is easier for respondents to recall, although it is recognized that experience may be acquired informally.…”
Section: Data Collectionmentioning
confidence: 99%
“…Saggaf, Salam, Kahar, & Akib, 2014;Salam, 2015;Salam & Rosdiana, 2016). The figure of a leader is the thing that most supports the success of an organization (Adams, 2011;Kragt & Guenter, 2018;Mascia, Dal Pubel, & Sartori, 2013;Nasila & Akib, 2014;"Organizational Effectiveness," 2013). Therefore, a leader, of course, must have special expertise so that he is able to oversee every vision and mission that is the goal of the organization.…”
Section: Introductionmentioning
confidence: 99%